Case report on surgical repair of unusual dissection of arterial duct involving main pulmonary artery in a child with vein of Galen malformation. Issue 4 (24th November 2018) - Muthialu, Nagarajan; Robertson, Alex; Mortensen, Kristian; Khambadkone, Sachin
Abstract: Background: Dissection involving patent arterial duct (PDA) extending to main pulmonary artery (MPA) is an extremely rare condition. Case summary: We report a case of complex dissection involving PDA extending to MPA, in a child with vein of Galen malformation. This was surgically corrected under deep hypothermic circulatory arrest, and we describe the pathophysiology and surgical rationale in this report. Discussion: Management of intracardiac lesion in the presence of intracranial arterio-venous malformations such as vein of Galen is very difficult, and employing deep hypothermic circulatory arrest allows one to manage cerebral protection while offering the visualization of intracardiac anatomy more effectively.